2021
DOI: 10.1111/lang.12475
|View full text |Cite
|
Sign up to set email alerts
|

Proficiency Reporting Practices in Research on Second Language Acquisition: Have We Made any Progress?

Abstract: Given that 10 years have passed since the publication of the most recent synthesis of proficiency assessment standards, the present review revisits proficiency assessment practices in research on second language acquisition (SLA), with the goal of examining whether the way in which scholars measure and report proficiency has changed. Our sample included 500 studies from five major SLA‐related journals published between 2012 and 2019. The findings indicate that whereas over 90% of the studies assessed and repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 71 publications
2
25
0
Order By: Relevance
“…A wide range of instruments was adopted in the included studies and there was a lack of detailed explanation of participants’ L2 proficiency levels (see Park, Solon, Dehghan‐Chaleshtori, & Ghanbar, 2021, for a synthesis showing similar reporting issues across L2 research more widely). Therefore, we divided the participants in the studies into “basic” and “beyond basic,” although we acknowledge that this may be an oversimplified perspective on L2 proficiency levels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of instruments was adopted in the included studies and there was a lack of detailed explanation of participants’ L2 proficiency levels (see Park, Solon, Dehghan‐Chaleshtori, & Ghanbar, 2021, for a synthesis showing similar reporting issues across L2 research more widely). Therefore, we divided the participants in the studies into “basic” and “beyond basic,” although we acknowledge that this may be an oversimplified perspective on L2 proficiency levels.…”
Section: Methodsmentioning
confidence: 99%
“…We would also encourage primary researchers to give more details about the moderator variables they include in their studies. For example, more detailed descriptions of the type of TVLE (e.g., the quantity and contents of TVLE) and the sampled students’ L2 proficiency levels (see Park et al., 2021, for further discussion) would enable future meta‐analysts to better capture the original variations related to these variables across the target studies. Such efforts, along with a greater number of future studies on this issue, would extend what the current meta‐analysis has presented to advance the understanding of the effects of TVLE on L2 vocabulary learning.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Beyond their value to a learner's own metacognition, self‐assessments are attractive to language teachers and testers as quick and convenient estimates of learner abilities and/or as important components in learning‐oriented assessments designed to raise learners’ awareness for the purposes of setting learning goals (Alderson, Brunfaut, & Harding, 2015; Butler & Lee, 2010). In addition, self‐assessment of proficiency is also used in L2 research for descriptions of participant characteristics (for a recent synthesis of proficiency reporting practices, see Park, Solon, Dehghan‐Chaleshtori, & Ghanbar, 2021, who found that 10.7% of the 500 studies that they surveyed used self‐ratings).…”
Section: Introductionmentioning
confidence: 99%
“…Second, we found a need for additional research investigating the effects of spacing on L2 learning that (a) involves young learners, (b) targets L2 grammar and pronunciation learning, (c) includes production activities, (d) includes delayed feedback, and (e) measures productive knowledge. Moreover, there is a need for clearer reporting of participants' L2 proficiency (as also observed in the synthesis by Park, Solon, Dehghan-Chaleshtori, & Ghanbar, 2021), which could help teachers to understand how learner differences may interact with the effects of spaced practice. Although learners may be learning through the same activities across and within courses, their L2 proficiency (and aptitude) will vary.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%